PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS ETNOMATEMATIKA PADA BANGUNAN MASJID AGUNG AL-FALAH DI JAMBI MATERI BANGUN RUANG KELAS V SD - Wirda, Aina; Maryono, Maryono; Hayati, Suci (Universitas Bhinneka PGRI, 2024)
This research aims to describe the development procedures, level of validity and practicality of ethnomathematics-based interactive multimedia in the Al-Falah Grand Mosque in Jambi building for class V elementary school building materials using the Lumio by SMART application. The approach applied is Research and Development (RD) with the ADDIE development model which includes analysis, design, development, implementation and evaluation. The research results show that the multimedia developed is very valid and practical. Validation by design experts got a score of 4.37 (very valid), material validation got an average score of 4.5 (very valid), validation by media experts got an average score of 4.4 (very valid), and validation by experts language obtained an average score of 4.35 (very valid). The teacher response questionnaire showed an average score of 5 (very practical), while the student response questionnaires in small and large group trials respectively obtained an average score of 4.55 and 4.52 (very valid). In conclusion, this ethnomathematics-based interactive multimedia is very valid and practical for use in class V elementary school classroom learning.